Pendampingan Sekolah Online Siswa SD pada Masa Pandemi Covid 19 sebagai Solusi Mengatasi Pendidikan di Pedesaan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Social problems are deeply rooted in every country, including Indonesia. This problem has spread to all fields, one of which is education. In addition, the COVID-19 pandemic situation has also given rise to many new problems in the world of education. Learning implemented during this pandemic has created a new learning transformation from offline to online. 80% of parents of SDN Kajuara I, II and III stated that their children had difficulty understanding the material when learning online. Online School Assistance through SIPUNG is a concrete solution to improve the quality and understanding of student learning during online learning. By using the service learning method, it has been proven to improve the quality and understanding of students, students understand the importance of learning and parents are increasingly aware of the importance of providing the best assistance to achieve the success of their children's education.